Energy, exergy and exergoeconomic analysis of high temperature short time milk pasteurisation plant. (5th July 2019) - Singh, Gurjeet; Singh, P.J.; Tyagi, Vineet V.; Barnwal, P.; Pandey, A.K.
India produces 19.54% of the total annual milk production of the entire world (819 MT) with yearly rise of 3.6%. The thermal and electrical energies consume 10%-20% of manufacturing cost of pasteurised milk. In the present work, energy, exergy and exergoeconomic appraisals of skim milk pasteurisation plant have been performed. The exergy gauge registered an exergy efficiency of 68.84% with 35% exergy recovery potential. The analysis revealed that relative irreversibility ratio of regeneration-3 (7.87%) was higher than regeneration-2 (4.24%) followed by regeneration-1 (1.25%), which represented their excellent sustainability characteristics. The thermoeconomic analysis has identified the immensity of exergoeconomic indices such as total operating cost rate, exergoeconomic factor and percentage relative cost difference. The exergoeconomic factor was reported to be most significant in holding coil (62.45%), heat exchanger (49.25%) and regeneration-1 (20.18%). The high and low values of exergoeconomic factor magnify the role of capital investment and thermodynamic inefficiencies respectively.